Stem Cell-Based Dental Tissue Engineering - Petar Zivkovic; Vladimir Petrovic; Stevo Najman; Vladisav Stefanovic (The Scientific World Journal)
The development of biological and biomaterial sciences profiled tissue engineering as a new and powerful tool for biological replacement of organs. The combination of stem cells and suitable scaffolds is widely used in experiments today, in order to achieve partial or whole organ regeneration. This review focuses on the use of tissue engineering strategies in tooth regeneration, using stem cells and stem cells/scaffold constructs. Although whole tooth regeneration is still not possible, there are promising results. However, to achieve this goal, it is important to understand and further explore the mechanisms underlying tooth development. Only then will we be able to mimic the natural processes with the use of stem cells and tissue engineering techniques.